2011
DOI: 10.1093/pcp/pcr027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Water Transport Mediated by PIP Aquaporins and Their Regulation Via Phosphorylation Events Under Salinity Stress in Barley Roots

Abstract: Water homeostasis is crucial to the growth and survival of plants under water-related stress. Plasma membrane intrinsic proteins (PIPs) have been shown to be primary channels mediating water uptake in plant cells. Here we report the water transport activity and mechanisms for the regulation of barley (Hordeum vulgare) PIP aquaporins. HvPIP2 but not HvPIP1 channels were found to show robust water transport activity when expressed alone in Xenopus laevis oocytes. However, the co-expression of HvPIP1 with HvPIP2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
146
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 63 publications
6
146
0
3
Order By: Relevance
“…The specificity of antibodies used to detect HvPIP2;1 and HvPIP2;2 has been shown previously (Horie et al, 2011).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The specificity of antibodies used to detect HvPIP2;1 and HvPIP2;2 has been shown previously (Horie et al, 2011).…”
Section: Resultsmentioning
confidence: 69%
“…Polyclonal antibodies for HvPIP2s were raised in rabbits against synthetic oligopeptides (Medical & Biological Laboratories Co., Tokyo, Japan) corresponding to the amino acid sequences in the N-region of HvPIP2;1 (Katsuhara et al, 2002), HvPIP2;2 (Horie et al, 2011) and HvPIP2;5 (EVMETGGGGDFAAKD, in the present study).…”
Section: Generation Of Antibodies Against Aqps Protein Expression Inmentioning
confidence: 99%
See 1 more Smart Citation
“…PIPs have been shown to be primary channels mediating water uptake in plant cells. HvPIP2 has been shown to transport water and have the ability to mediate water loss from plant cells under salt stress (Horie et al, 2011). NIPs only exist in plants and can transport different substrates, not only water, glycerol (Dean et al, 1999), and lactic acid (Choi and Roberts, 2007) but also large solutes such as urea (Wallace and Roberts, 2005), boron, silicon, and arsenic (Mitani-Ueno et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Antisense inhibition experiments on Arabidopsis thaliana PIP1 and PIP2 have suggested that the two subgroups of aquaporins contribute to root or leaf hydraulic conductivity in the same way (13). In several plant species, members of the PIP1 and PIP2 subgroups were shown to be coexpressed in the same cell type (14)(15)(16)(17).…”
mentioning
confidence: 99%